Planning for Intangible Cultural Heritage in Tourism: Challenges and Implications. (September 2019) - Esfehani, Minoo H.; Albrecht, Julia N.
This empirical article is the first to consider tourism planning for tourism products based on intangible cultural heritage (ICH). It identifies two sets of factors that affect related tourism planning, the accessibility of ICH-based tourism products for visitor market(s), and the perceived appropriateness of ICH for use in tourism. The factors are derived using a qualitative, ethnographic method, implemented in the Qeshm Island Global Geopark in the South of Iran. Theoretical and practical implications address the requirements for tourism planners to extend the tourism planning arena, the integration of planning efforts for tourism and heritage preservation, and the need to involve stakeholders who co-create value from both tourism and heritage preservation perspectives. The impact of the article lies not only in its originality but also in its contributions to the literature on cultural (heritage) tourism as well as tourism planning.